John H. Dent order-book - Dent, John H. (John Herbert), 1782-1823.
Order-book kept by Capt. John H. Dent aboard the USF Constitution and the USS John Adams. Includes orders issued by Samuel Barron, Hugh G. Campbell, Paul Hamilton, Edward Preble, and John Rodgers.
Naval officer.
Collection material in English.
Forms part of: Naval Historical Foundation collection.
Keywords: Barron, Samuel, -- -1810.; Campbell, Hugh G. -- 1760-1820.; Hamilton, Paul, -- 1762-1816.; Preble, Edward, -- 1761-1807.; Rodgers, John, -- 1773-1838.; Constitution (Frigate); John Adams (Ship); United States. -- Navy; United States. -- Navy -- Order-books.; Ship's papers -- 19th century; Naval officers